11β-Hydroxysteroid Dehydrogenase Type 2 Polymorphisms and Activity in a Chilean Essential Hypertensive and Normotensive Cohort - Campino, Carmen; Quinteros, Hector; Owen, Gareth I.; Carvajal, Cristian A.; Morales, Mauricio; Olivieri, Oliviero; Guidi, Giancesare; Faccini, Giovanni; Pasini, Francesco; Baudrand, Rene; Padilla, Oslando; Valdivia, Carolina; et al. (American journal of hypertension, 2012)
Background 11β-hydroxysteroid dehydrogenase type 2 enzyme (11β-HSD2) inactivates cortisol (F) to cortisone (E); its impairment is associated with hypertension. We reported that 15.7% of the Chilean essential hypertensives possessed a high F/E ratio suggesting a partial deficit in 11β-HSD2 activity. It has been reported that the G534A(Glu178/Glu) polymorphism in the HSD11B2 gene is associated with hypertension. Investigate the frequency of the G534A polymorphism and its correlation with the glucocorticoid profile in Chilean essential hypertensive and normotensive subjects. Methods Essential hypertensive outpatients (n = 232) and normotensive subjects (n = 74) were recruited. A change in the AluI restriction enzyme digest pattern, caused by the presence of the G534A polymorphism, was utilized to screen DNA isolated from leukocytes within the cohort before confirmation by sequencing. Plasma renin activity (PRA), serum aldosterone, F, and E were measured by radioimmunoassay. Urinary tetrahydrocortisol (THF), 5α-tetrahydrocortisol (5α-THF), and tetrahydrocortisone (THE) were measured by gas chromatography-mass spectrometry. Results G534A polymorphism frequency was similar between hypertensive patients (19 of 232; 8.2%) and normotensive subjects (7 of 74; 9.5%). When categorized by presence or absence of the G534A polymorphism, no significant differences in the serum F/E ratio or other measured biochemical variables were detected. Despite a previous report that the G534A polymorphism is associated with a neighboring C468A (Thr156/Thr) polymorphism, analysis within our cohort showed that only one patient in each group presented with this double polymorphism. Conclusions We report the frequency of the G534A polymorphism in the Spanish-Amerindian population. No correlation was detected between this polymorphism and the presence of hypertension and biochemical parameters in this Chilean cohort.